Perspektif Hukum Ekonomi Syariah Terhadap Penerapan Akad Wakalah di UPZ IAIN Madura - Afandi , Moh; Zahroh, Fatimatuzzahrah (Al-Hiwalah: Journal of Sharia Economic Law, 2023)
Wakalah guard, guarantee, dependents, power of attorney. And also wakalah contract can be interpreted as the delegation of power by a person as the first party to another person as a second party in matters being represented (in this case the second party) only carries out something limited or the authority granted by the first party, but if the power has been carried out as required, then all risks and responsibilities for the implementation are fully carried out by the first party or the power of attorney. The research focus of this research is on the Application of Wakalah Contracts at UPZ IAIN Madura and how the application of Wakalah Contracts in the perspective of sharia economic law at UPZ IAIN Madura. In this study, the researcher used a qualitative research method, namely research that was intended to examine in a sharia way the application of the wakalah contract at UPZ IAIN Madura, where the phenomena experienced by subjects were empirical legal research or field research. Sources of data obtained through interviews, observation and documentation. The informant is the management of UPZ IAIN Madura (amil zakat). Then the data analysis technique used is starting from Data Reduction, Data Presentation and Conclusion. The research results of the wakalah contract applied at UPZ Madura are in accordance with the regulations of all UPZ IAIN Madura work programs which are in accordance with the meaning of the wakalah contract, namely the handing over of the mandate from muzakki to UPZ IAIN Madura. The requirement to become a manager must be truly trustworthy as one must be able to trust and be transparent in the management of ZIS finances (Zakat, Infaq and Sedekah). Muzakki who have donated their funds to UPZ IAIN Madura means that they have trusted UPZ IAIN Madura to be able to manage the funds from Muzakki. As a contribution from zakat managers which UPZ IAIN Madura must manage and distribute properly. Seeing from sharia economic law, the application of the wakalah contract at UPZ IAIN Madura has been carried out well. Because, looking at all aspects that occur related to zakat, infaq and alms, it is included in the special provisions in Islamic law. With this wakalah contract, Muzakki does not arbitrarily give trust to UPZ IAIN Madura to manage and distribute these funds to those in need. UPZ IAIN Madura provides funding facilities from orphans, the dhuafa and the poor/poor people